Up‐and‐down shift in residence depth of slickheads (Alepocephalidae) revealed by otolith stable oxygen isotopic composition. Issue 3 (29th January 2016) - Shiao, J. C.; Liu, E. Y.; Sui, T. D.
Abstract : Otolith δ 18 O profiles for four slickhead species (Alepocephalidae) suggested that Alepocephalus umbriceps, Talismania okinawensis and Rouleina watasei migrated hundreds of metres to shallower depths during the juvenile to young stages before returning to their original depth or even deeper waters. Xenodermichthys nodulosus gradually shifted residence depth from shallow to deeper water during their life. These migratory patterns indicated that the slickheads examined had allopatric residence depths at different life stages, which might enhance the pelagic survival and growth rates of the juvenile and young fishes.